Affect intensity and softness tactile preferences: An experimental approach to arousal regulation. (September 2016) - Kergoat, M.; Giboreau, A.; Nicod, H.; Faye, P.; Diaz, E.; Beetschen, M.A.; Meyer, T.
Highlights: High Affect Intensity people have a preference for soft textiles. Such an attitude serves a need for positive stimulation in a poor arousal context. Arousal context manipulation affects sensory tactile preferences. Abstract: Previous findings have shown that people experiencing emotions more intensely present favorable attitudes toward tactile softness. Based on Larsen's (2009) hypothesis that a higher level of affect intensity is a way to compensate for a low level of baseline arousal, we suggest that such a positive attitude toward soft textiles serves a need for stimulation in a poor arousal context (e.g., Central Location Test; CLT). An experimental study was run using the IAPS (Lang, Bradley, & Cuthbert, 2005) in order to manipulate the arousal context prior to a sensory evaluation of textiles. Significant results were observed on one component of the Affect Intensity Measure (Larsen & Diener, 1987). As expected, in the low arousal condition, participants characterized by higher levels of intensity in positive emotions showed a preference for softer textiles, whereas this effect was not observed in the high arousal condition. Theoretical and practical implications of these results are discussed.